Reading Comprehension and Test-Taking Strategies of Different Achievement Levels - Irawan, Lalu Ari; Ahmad, Ramli (Universitas Muhammadiyah Yogyakarta, 2000)
The complexity of the reading process, which poses significant challenges for EFL and ESL learners, underpins this research into effective strategies for both reading comprehension and answering English reading texts. This qualitative phenomenological research aimed to explore the strategies that students use during reading activities and while taking reading comprehension tests. The study involved four fourth-semester students, differentiated by gender and achievement levels: a high-achieving female, a low-achieving female, a high-achieving male, and a low-achieving male. The research identified that students employed a variety of strategies, with 11 metacognitive strategies being used out of a possible 23, including determining word meaning, making connections, inferring, and summarizing. Additionally, four out of the five FIVES reading strategies were utilized: inference, vocabulary, summarization, and experience. High-achieving students employed more strategies, leading to better comprehension and higher test scores. For test-taking, strategies such as careful time management, revisiting difficult questions, and employing process-of-elimination techniques were noted. The effectiveness of both reading and test-taking strategies, along with factors like topic familiarity and the ability to make inferences, were crucial in determining reading success. These findings underscore the importance of targeted interventions that focus on teaching effective strategies, enhancing topic familiarity, and supporting students in developing robust test-taking strategies, particularly for low-achieving students.